2023
DOI: 10.3390/agriculture13020456
|View full text |Cite
|
Sign up to set email alerts
|

Matrilineal Composition of the Reconstructed Stock of the Szekler Horse Breed

Abstract: The Szekler horse was a small-sized mountain horse of the Carpathian Mountains whose official stud book ceased to exist after WWII. Despite that, individual horses preserving all the characteristics of the Szekler horse remained scattered in remote areas. This study aims to evaluate the mitochondrial D-loop sequence (608 bp) of the founder population (n = 59) in 2021 of a breed reconstruction project started in 2012. D-loop showed 68 polymorphic sites. The number of haplotypes was 34, with haplotype diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Even if the whole genomic approaches are now opening up new clues on livestock complexity and admixture, the mitochondrial DNA (mtDNA) and the male-specific region of the Y chromosome (MSY) continue to be extremely important sources of information because of their unique pattern of inheritance, as demonstrated in different species such as sheep and goat [ 1 , 2 , 3 , 4 ], cattle [ 5 , 6 , 7 , 8 ], and horse [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the whole genomic approaches are now opening up new clues on livestock complexity and admixture, the mitochondrial DNA (mtDNA) and the male-specific region of the Y chromosome (MSY) continue to be extremely important sources of information because of their unique pattern of inheritance, as demonstrated in different species such as sheep and goat [ 1 , 2 , 3 , 4 ], cattle [ 5 , 6 , 7 , 8 ], and horse [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies reported that the Iberian Peninsula was also possibly the site of horse domestication ( Lopes et al, 2005 ). One of the recent studies reported that there are 18 haplogroups based on horse mtDNA (A-R) and majority of them were domesticated in Asia ( Gáspárdy et al, 2023 ). They were not well differentiated geographically due to the mixing and modern breeding methods.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used as carriers during prehistorical times and have undergone considerable breed mixing leading to a significant alteration in their genetic structure. However, mtDNA plays a key role in determining the origin of breeds ( Gáspárdy et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%